Investigação das propriedades estruturais e dielétricas da matriz YVO4 e seus compósitos (YVO4-TiO2) como função da temperatura para aplicações em engenharia de micro-ondas - Sousa, Wellington Viana de (2023)
The study of the electric properties of ceramics has increased with the development of sectors such as electronics, telecommunications, and computing. Yttrium orthovanadate (YVO4) is a ceramic material that has been widely investigated for its optical properties, but its electrical properties have been little explored. This work describes the synthesis, structural characterization, and investigation of the dielectric behavior in the radiofrequency (RF) and microwave (MW) region of YVO4 in the form of a composite with TiO2: YVO4-TiO2 (YVTx, with x=10, 20, 30 and 40 mol% TiO2). The materials were also evaluated as dielectric resonator antennas (DRA). Through X-ray diffraction and Rietveld refinement, it was confirmed that YVO4 was obtained as a pure phase. For the composites, the presence of TiO2 and Y2Ti2O7 was confirmed as a secondary phase in small proportion, varying between 1.15 and 3.62% by weight. The electrical behavior in RF by impedance spectroscopy indicated the presence of thermally activated processes between 200 and 440 °C. Between 100 and 180 °C, the typical behavior of a material with a positive temperature coefficient of resistivity (PTCR) was identified. At room temperature, YVO4 and the composites exhibited colossal ε' (> 104) in the low-frequency region (f < 100 Hz) being attributed to space charge polarization processes and presented tan δ < 1 (loss tangent) when f > 100kHz. The variation of conductivity with frequency followed Jonscher’s law. The Nyquist diagrams were well adjusted using an equivalent electrical circuit consisting of a resistor element (R) connected in parallel by a phase constant element (CPE) and combined in series with another R-CPE system, indicating the grain and boundary region grain of the material. The YVT40 at 10 kHz with a Capacitance Temperature Coefficient (TCC) of -24 ppm°C-1 and the YVT20 at 10 MHz (TCC = 20 ppm°C-1) presented the best thermal stability of the capacitance in RF. The composites also had their dielectric properties characterized in the MW region using the Hakki-Coleman technique and the resonance frequency temperature coefficient (τf) was determined using the Silva-Fernandes-Sombra method. The composites presented εr ≈ 12 and tan δ between 10-2 and 10-3. YVT20 exhibited high thermal stability of the resonant frequency with τf = 6.96 ppm °C-1. In DRA and numerical simulation tests, YVT20 exhibited high radiation efficiency (95.49%), making it a promising candidate for wireless communication applications operating in the C band (4 – 8 GHz).